Understanding and predicting the geographic distributions of phlebotomine sand flies in and around Europe - CLIMOS data providers (2025)
Climate and land-use changes influence the transmission of vector-borne diseases by affecting the distribution and survival of disease vectors. Numerous diseases are transmitted by phlebotomine sand flies (Diptera: Psychodidae: Phlebotominae), including leishmaniasis. Several major sand fly-borne diseases are responsible for high global disease burdens and high socio-economic costs. In Europe, over 20 known sand fly vector species are largely confined to the Mediterranean Basin, yet records of sand fly presence further north increase. Global warming is predicted to drive the spread of sand flies to large areas of Europe in the 21th century, an effect likely to be exacerbated by anthropogenic factors. However, the constraints to the geographic distributions of sand flies are not well understood. This study aims to increase the understanding of the drivers of the geographic distributions of sand flies, using species distribution modelling to systematically test links between sand fly occurrences and climatic, land-use, lithological, biodiversity and human population variables in Europe and adjacent Mediterranean regions. We found that moisture is the most important environmental variable both in explaining and in predicting sand fly occurrences. The projected suitable habitats are larger than the current known sand fly distributions, and these habitats are expected to expand due to changes in climate and land-use.